Comparison of the effectiveness of dialectical behavior therapy (DBT) and acceptance and commitment based therapy (ACT) on proactiveness, increasing self-esteem, reducing mental ruminations in adolescent boys between 12 and 18 years old in Tehran - Rahnamazadeh, Mojtaba; Ehsanpour, Fatemeh; Mohseni Nasab , Zahra; Ahangari , Zahra; Gayour, Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Life after parents’ divorce seems impossible for many children. Children of divorce will experience new negative emotions from the day of divorce onwards. These feelings are so fluctuating that sometimes they are confused and startled by the oppositeness of these feelings, and they will suffer from common feelings such as anxiety, loneliness, and tendency to addiction. Therefore, the aim of the current research was to compare the effectiveness of schema therapy and acceptance and commitment ACT therapy in reducing anxiety, loneliness and the tendency to addiction in male adolescents with divorced parents. The research method is practical in terms of purpose and semi-experimental in terms of data collection method. The statistical population of this research includes male teenagers with divorced parents in Qom city. According to the nature of the study method, the statistical sample size of this part of the research was 30 people. The research tools are UCLA Anxiety Questionnaire and Loneliness Questionnaire, Wade and Butcher Addiction Tendency Questionnaire, schema therapy and treatment based on acceptance and commitment. Based on the findings of the current research, it was determined that schema therapy was effective on the anxiety of male adolescents with divorced parents, therapy based on acceptance and commitment was effective on the anxiety of male adolescents with divorced parents, and schema therapy was effective on the loneliness of male adolescents with divorced parents. Treatment based on acceptance and commitment has been effective on the loneliness of male adolescents with divorced parents, schema therapy has been effective on the addiction tendency of male adolescents with divorced parents, treatment based on acceptance and commitment has been effective on the addiction tendency of male adolescents with divorced parents have been; It was also found that the treatment based on acceptance and commitment was more effective than schema therapy.